Performance Trade-Offs in Wild White-Footed Mice (Peromyscus Leucopus) - Berberi, Ilias (Université d'Ottawa / University of Ottawa, 2018)
Various aspects of performance (e.g., sprint speed, grip strength) are thought to be important determinants of the success of animals in natural activities such as foraging, mating, and escaping from predators. However, it is generally known that morphological properties enhancing one type of performance (e.g., speed) can lead to a reduction in another (e.g., strength). Such performance trade-offs have been quantified at the inter-specific level, but evidence at the inter-individual level remains equivocal. To test for the presence of a performance trade-off, I initiated a study on wild white-footed mice (Peromyscus leucopus). In summer 2016, I captured a total of 186 individuals, 87 of which were repeatedly phenotyped for grip strength and sprint speed. A significant positive relationship was found between body mass and grip strength (but not for sprint speed). Individual differences in performance were repeatable through time for both grip strength and sprint speed. Using a bivariate mixed model, I detected a significant negative correlation between grip strength and sprint speed at the among-individual level. By contrast, the within-individual correlation between grip strength and sprint speed tended to be positive, suggesting that some unquantified aspects of the mouse phenotype (e.g., body condition, age) may have a positive effect on both performance traits. Given the relatively low repeatability of grip strength and sprint speed, a failure to properly partition the correlation at the among- and within-individual level generates a counter-intuitive, positive correlation. This study is one the first to detect a performance trade-off at the among-individual level in a wild animal population.
Keywords: Performance; Trade-off; Repeatability; Peromyscus; Correlation; Grip strength; Sprint speed; Wild